2019
DOI: 10.1155/2019/6707650
|View full text |Cite
|
Sign up to set email alerts
|

Associations between TLR4 Polymorphisms and Open Angle Glaucoma: A Meta-Analysis

Abstract: Background. Previous studies exploring the association between toll-like receptor 4 (TLR4) polymorphisms and open angle glaucoma (OAG) presented inconsistent results. We aimed to investigate the association between TLR4 polymorphisms and OAG. Methods. A systematic literature search was conducted in PubMed, EMBASE, ISI Web of Knowledge, and the Cochrane Library up to 31 December 2018. Odds ratio (OR) and 95% confidence interval (95%CI) were calculated, followed by stratification analyses according to ethnicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…TLR4 gene rs4986790 polymorphism confers different susceptibility on various diseases. A number of studies have shown that TLR4 rs4986790 polymorphism is associated with risk of multiple diseases such as pneumonia, open angle glaucoma, cancer, Type 2 diabetes and Inflammatory Bowel Disease 21 , 22 , 23 , 24 . And TLR4 rs4986790 polymorphism is not associated with risk of asthma, coronary artery disease, atherosclerosis or preeclampsia 25 , 26 , 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR4 gene rs4986790 polymorphism confers different susceptibility on various diseases. A number of studies have shown that TLR4 rs4986790 polymorphism is associated with risk of multiple diseases such as pneumonia, open angle glaucoma, cancer, Type 2 diabetes and Inflammatory Bowel Disease 21 , 22 , 23 , 24 . And TLR4 rs4986790 polymorphism is not associated with risk of asthma, coronary artery disease, atherosclerosis or preeclampsia 25 , 26 , 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are the largest health care practitioners and through their care activities can apply the results of genetic laboratory research to clinical applications. Health education is an important way 22 . Change bad living habits, such as smoking, drinking, high‐salt and high‐fat diet, lack of exercise, etc., and cultivate scientific harmony and Rational life style is an important content of hypertension health education.…”
Section: Discussionmentioning
confidence: 99%
“…The connection of Toll like receptor-4 (TLR-4) and its ligand lipopolysaccharide (LPS) with IRI or glaucoma has been demonstrated in previous studies, showing that genetic deletion of TLR-4 is neuroprotective in IRI disorders ( 23 ). Furthermore, mutations on the TLR-4 correlated with altered susceptibility to primary open angle glaucoma and were even described as a possible bio-indicator ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, TLRs pathway induce glaucomatous neuroinflammation in two ways, either through polymorphism of TLR4 alleles [ 67 ] or increase in TLR4 protein expression in the retina of glaucoma animal models [ 68 ]. Different TLRs recognize different stimuli.…”
Section: Main Textmentioning
confidence: 99%